Investigating the citing communities around three leading health-system frameworks - George Weisz; Jonathan Harper (BMC, 2024)
Abstract Of numerous proposed frameworks for analyzing and impacting health systems, three stand out for the large number of publications that cite them and for their links to influential international institutions: Murray and Frenk (Bull World Health Organ 78:717-31, 2000) connected initially to the World Health Organization (WHO) and then to the Global Burden of Disease Project; Roberts et al. (Getting health reform right: a guide to improving performance and equity, Oxford University Press, Oxford, 2004) sponsored by the World Bank/Harvard Flagship Program; and de Savigny and Adam (Systems thinking for health systems strengthening, WHO, 2009) linked to the WHO and the Alliance for Health Policy and Systems Research. In this paper, we examine the citation communities that form around these works to better understand the underlying logic of these citation grouping as well as the dynamics of Global Health research on health systems. We conclude that these groupings are largely independent of one another, reflecting a range of factors including the goals of each framework and the problems that it was meant to explore, the prestige and authority of institutions and individuals associated with these frameworks, and the intellectual and geographic proximity of the citing researchers to each other and to the framework authors.